Non-adherence in non-inferiority trials: pitfalls and recommendations. (1st July 2020) - Mo, Yin; Lim, Cherry; Watson, James A; White, Nicholas J; Cooper, Ben S
Abstract : Non-adherence in non-inferiority trials can affect treatment effect estimates and often increases the chance of claiming non-inferiority under the standard intention-to-treat analysis. This article discusses the implications of different patterns of non-adherence in non-inferiority trials and offers practical recommendations for trial design, alternative analysis strategies, and outcome reporting to reduce bias in treatment estimates and improve transparency in reporting.